Developing Mathematics Written Communication through Case-Based Learning - Suratno, Joko; Hamid, Ikram; Waliyanti, Ida Kurnia (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Mathematical education, as it is now practiced, has many problems. Students that were taught using traditional instruction were only taught to listen. Without the input and feedback of the pupils, the teacher controls the learning process. Students were unable to improve their communication abilities and lacked learning independence. This study aimed to ascertain how case-based learning affected students' mathematics communication skills. The study had a posttest-only design and was a quasi-experimental investigation. The control class received standard instruction, whereas the experiment class received case-based learning instruction. The ability of students to communicate mathematically was the dependent variable in this study. The independent variables in this study were case-based learning and independent variables. Forty-six pre-service mathematics teachers from two full classes served as the research participants in their fifth semester. The tests of prior knowledge and mathematical communication skills were used as study tools. According to the research findings, there is a difference in students' capacity for mathematical communication between those who receive case-based learning instruction and those who receive traditional instruction. The experiment class had better student communication skills than the control group (p-value = 0.047). As a result, case-based learning is one option for enhancing students' communication abilities.